Igbo Animated Cartoon Videos as a veritable Instructional tool for Enhancing Upper Basic Students’ Proficiency in Igbo in Lagos, Nigeria - Okeke, Nkechi Ursula; Opara, Carole C. (NIU Journal of Social Sciences, 2018)
This study examines the use of Igbo animated cartoon as a veritable instructional tool for enhancing upper basic studentsâ€™ proficiency in Igbo. The study used a quasi-experimental research design which made use of pre-test/ post- test method; a comparison was made between teacher didactic instructional based method of teaching and Igbo animated cartoon based instructional method of teaching. A hundred and eight (108) upper basic 7 Igbo students and four (4) Igbo language teachers from a Federal Government College in Lagos made up the population of the study.  Two intact classes of 54 students each constituted the sample which was selected using purposeful sampling technique. Two sets of questionnaires for both teachers and students and structured oral interview for teachers were also used in collecting data for the study. Data were analyzed using descriptive and inferential statistics while the hypotheses were tested using the t-test statistics. Result from the pre-test and post â€“test that tested the upper basic students on the four language skills indicated that the treatment group was highly motivated to learn Igbo language leading to a better proficiency in Igbo language than the control group at the end of the study.     The study therefore, recommended that schools should encourage their teachers to make use of animated cartoon to motivate their students and make teaching/ learning of Igbo language more interactive, more interesting and less difficult for students. Keywords:  animated cartoons, development, instructional tool, proficiency and Igbo language.